2015
DOI: 10.1007/s11356-015-4394-x
|View full text |Cite
|
Sign up to set email alerts
|

Elements and polycyclic aromatic hydrocarbons in exhaust particles emitted by light-duty vehicles

Abstract: The main purpose of this work was to evaluate the chemical composition of particulate matter (PM) emitted by eight different light-duty vehicles. Exhaust samples from petrol and diesel cars (Euro 3 to Euro 5) were collected in a chassis dynamometer facility. To simulate the real-world driving conditions, three ARTEMIS cycles were followed: road, to simulate a fluid traffic flow and urban with hot and cold starts, to simulate driving conditions in cities. Samples were analysed for the water-soluble ions, for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 83 publications
5
37
2
Order By: Relevance
“…In comparison, the total carbon emissions in this study are lower than those in previous studies, whereas the WSIs and elements fractions are higher (Alves et al, 2015a;Cui et al, 2016;Schauer et al, 1999;Wu et al, 2016). Several factors have influenced these differing results such as fuel quality, driving condition, engine parameters (fuel injection timing, compression ratio, and fuel injector design), and experimental methods (Sarvi et al, 2008a(Sarvi et al, , b, 2009Sarvi and Zevenhoven, 2010).…”
Section: Average Source Profile Of Pm For Truckscontrasting
confidence: 73%
“…In comparison, the total carbon emissions in this study are lower than those in previous studies, whereas the WSIs and elements fractions are higher (Alves et al, 2015a;Cui et al, 2016;Schauer et al, 1999;Wu et al, 2016). Several factors have influenced these differing results such as fuel quality, driving condition, engine parameters (fuel injection timing, compression ratio, and fuel injector design), and experimental methods (Sarvi et al, 2008a(Sarvi et al, , b, 2009Sarvi and Zevenhoven, 2010).…”
Section: Average Source Profile Of Pm For Truckscontrasting
confidence: 73%
“…However, K is also present in unleaded fuels (Spencer et al, 2006) or used as an additive in some types of oil and as an antifreeze inhibitor. Recent chassis dynamometer studies also showed K can be an important component of direct tailpipe emission (Alves et al, 2015). The distinct existence of K in Factor 2 indicates their possible tailpipe origin for the local vehicle fleets in Hong Kong, rather than other sources.…”
Section: Source Apportionmentmentioning
confidence: 98%
“…Polycyclic aromatic hydrocarbons (PAHs) are created by incomplete combustion or pyrolysis at high temperature under oxygen deficiency during the engine combustion process. In conventional diesel combustion, the semi-volatile fractions of exhaust gas samples are dominated by PAHs and their homologues alkylation series [26]. As illustrated in Figure 3 and Table 3, the peak time of corresponding species is in the range from 3.544 min to 41.062 min, and the main 41 species are identified based on matching degree.…”
Section: Gc-ms Detection Of Unregulated Emissionsmentioning
confidence: 99%
“…Figure 4 is TIC of unregulated emissions absorbed by absorption liquid in conventional diesel combustion, and Table 4 lists the main exhaust components in the order of retention time. Volatile organic compounds (VOCs) in the C 6 -C 11 range of diesel engine exhaust gas have been reported in literature [26], while little studies on heavy components with longer carbon chains were discussed. As shown in Figure 4 and Table 4, the retention time of corresponding species is in the range from 2.298 min to 28.782 min, and about 21 species are identified on account of matching degree.…”
Section: Gc-ms Detection Of Unregulated Emissionsmentioning
confidence: 99%